Penerapan Model Discovery Learning pada Pokok Bahasan Balok Dan Kubus untuk Meningkatkan Pemahaman Konsep Siswa - Anis Farida; Nur Farida; Vivi Suwanti (Indo-MathEdu Intellectuals Journal, 2023)
This research uses a qualitative approach which aims to determine the application of the discovery learning model to the subject of blocks and cubes to increase the conceptual understanding of class VIII students at SMP PGRI 02 Pakisaji. The subjects in this research were 16 students in class VIII for the 2023 school year. The data used are: concept understanding test results, observation results, interview results, and field notes. The data collection steps used in this research are: providing a concept understanding pretest, providing discovery learning and observation, concept understanding posttest, four interviews. The data analysis used in this research is: data reduction, data presentation, drawing conclusions and verification. The research results showed that the percentage of students' understanding of mathematical concepts increased from 9.95% in cycle I to 31.8% in cycle 2 with a KKM ≥70. Teacher and student activity during learning obtained a total average of 66% in cycle I, increasing to 88% in cycle II and student activity during learning obtained a score of 50% in cycle I, increasing to 85% in cycle II. Based on the research results, it can be concluded that Discovery Learning can improve students' understanding of concepts in class VIII